2022
DOI: 10.1038/s41598-022-11298-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and patient satisfaction with raloxifene/cholecalciferol combination therapy in postmenopausal women

Abstract: This study was performed to evaluate quality of life (QOL) and patient satisfaction with raloxifene/cholecalciferol combination therapy in postmenopausal women with low bone mass. This multicenter, prospective, noninterventional observational study included 3907 postmenopausal women who received a combination of raloxifene 60 mg and cholecalciferol 800 IU daily to treat or prevent osteoporosis. Changes in QOL and patient satisfaction were evaluated after 3 and 6 months of treatment. In addition, the safety pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have demonstrated a positive correlation between age and OP prevalence, with an incidence rate of 3.2% in individuals aged 40–49 and 32.5% in those aged 65 and above, highlighting the considerable risk OP poses to the physical and mental well-being of middle-aged and elderly individuals, substantially impacting their daily functioning 2 . Therefore, early detection and intervention, as well as effective control of the progression of osteoporosis, are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated a positive correlation between age and OP prevalence, with an incidence rate of 3.2% in individuals aged 40–49 and 32.5% in those aged 65 and above, highlighting the considerable risk OP poses to the physical and mental well-being of middle-aged and elderly individuals, substantially impacting their daily functioning 2 . Therefore, early detection and intervention, as well as effective control of the progression of osteoporosis, are essential.…”
Section: Introductionmentioning
confidence: 99%
“…4.2.7 Quality of LifeQuality of life is the ultimate destination of all medical research, and both osteoporosis and cognitive impairment lead to a decline in patients' quality of life(53). Osteoporosis can cause pain, fractures, and other health issues, affecting patients' daily life and mobility(54). Cognitive impairment may result in memory loss, slow thinking, and other neuropsychiatric symptoms, affecting patients' social skills, selfmanagement, and quality of life(55).…”
mentioning
confidence: 99%